Ida J. Smith to Dan Tompkins from January 24, 1947 - Masters, Jessica (2018)
This letter was written by Ida Jane Smith in January 1947. Within this letter, Ida Smith discusses the salaries she received as a pioneer schoolteacher in western North Carolina. The text of the letter recognizes that this letter may have been a part of a series of correspondences between Ida Smith and Dan Tompkins. After listing her salaries at various positions in different counties and schools, she continues to note that it has been difficult to gather all of the materials together she had been asked for. At the time that this letter was written, Ida Smith was nearly 74 years old.